Impediments to the implementation of voluntary codes of conduct in production factories of the Global South: so much to do, so little done. - Drebes, Maike J. (Third World Quarterly, 2014)
A common consequence of the fragmented supply practices of multinational corporations are unfair and exploitative working conditions in the global South. Many corporations face this, and the resulting reputational damage, by installing voluntary codes of conduct in their supplier factories, leading to a vast range of implementation practices by the factory managers. Despite this effort, the literature shows that the positive impact of these codes on labour conditions in such factories remains insufficient. This article argues that this insufficiency is rooted in the exclusiveness and eurocentrism of codes of conduct and elaborates on why corporations tend to prefer influencing certain labour conditions over others. It concludes by briefly discussing multi-stakeholder organisations as a possible solution to these predicaments, and points the way to further research on the topic.